PENINGKATAN PENGUASAAN KONSEP DAN AKTIVITAS BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE TGT (TIMES GAMES TOURNAMENT) PADA MATERI SISTEM SARAF DI SMA YABUJAH INDRAMAYU TAHUN 2020/2021 - Nur Isnaeni (Sinau : Jurnal Ilmu Pendidikan dan Humaniora, 2022)
The reality in the field shows that student learning activities are still low, low learning activities can affect the mastery of student concepts, low student participation when teaching and learning activities, students are less enthusiastic about the delivery of teaching materials conducted by teachers (models / methods do not vary), student motivation in learning is still low. Learning objectives can be in the form of an increase in mastery of concepts and an increase in student learning activities or an increase in other potential students have. The application of the TGT Cooperative Learning Model (Times Games Tournament) is expected to be a solution for solving passive learning problems. The results showed: students' mastery of concepts increased after applying the TGT model, this can be evidenced by the difference in the pre-test average value of 40.8 and the post-test average value of 74.3. In addition there are differences in the mastery of the concept of the experimental class and the control class. Measurement of learning activities of control class students get the highest value on the listening activities indicator while in the experimental class the highest indicator leads to emotional activities. The implementation of the TGT (Teams Games Tournament) cooperative learning model to improve the mastery of concepts and student learning activities as a whole can be carried out well and can facilitate learning activities. The application of the TGT cooperative learning model gets a positive response from students